2020
DOI: 10.1088/1757-899x/916/1/012104
|View full text |Cite
|
Sign up to set email alerts
|

Injection moulded composite bipolar plates for a portable hydrogen fuel cell charger

Abstract: Fuel cells are electrochemical devices that convert the chemical energy of a reactants directly into electricity and heat with high efficiency. Proton Exchange Membrane or Polymer Electrolyte Membrane (PEM) fuel cells are one of the most common type of fuel cells. In a convection PEM fuel cell, the oxygen from air is introduced to the cathode and hydrogen is introduced to anode. Between the anode and cathode electrodes is sandwiched the polymer electrolyte membrane. The hydrogen molecules break apart into prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Advantages of IM include low labor cost, minimal scrap losses, ability to use a wide range of materials to mold complex three-dimensional shapes easily, high precision, and short production cycles [55][56][57]. The main focus of most studies on injection-molded BPs is the development of composites that meet the performance requirements for PEMFC BPs [58][59][60][61][62]. Serban and Opran [59] conducted a study to compare the performance of injection-molded filled PP BPs in a single FC stack to that in which the gas channels were machined on a compression-molded thermoset resin/G composite plate.…”
Section: Injection Moldingmentioning
confidence: 99%
See 1 more Smart Citation
“…Advantages of IM include low labor cost, minimal scrap losses, ability to use a wide range of materials to mold complex three-dimensional shapes easily, high precision, and short production cycles [55][56][57]. The main focus of most studies on injection-molded BPs is the development of composites that meet the performance requirements for PEMFC BPs [58][59][60][61][62]. Serban and Opran [59] conducted a study to compare the performance of injection-molded filled PP BPs in a single FC stack to that in which the gas channels were machined on a compression-molded thermoset resin/G composite plate.…”
Section: Injection Moldingmentioning
confidence: 99%
“…The main focus of most studies on injection-molded BPs is the development of composites that meet the performance requirements for PEMFC BPs [58][59][60][61][62]. Serban and Opran [59] conducted a study to compare the performance of injection-molded filled PP BPs in a single FC stack to that in which the gas channels were machined on a compression-molded thermoset resin/G composite plate. The results revealed that the machined BPs exhibited a better performance for the voltage with no load (4.10 V) compared to the injectionmolded plates (3.92 V).…”
Section: Injection Moldingmentioning
confidence: 99%
“…125 San and Okur observed that high moulding temperatures led to the development of gas bubbles on polymer surfaces, which deforms the material. 126 Curing will be required to counteract the distortion; however, this will lead to an increase in manufacturing time and costs as reported by Taormina et al 127 In addition, in the long term, the economic situation of this production method must be examined more closely for any target application. An alternative manufacturing process based on injection moulding or hot stamping by rollers is currently under investigation and not commercially available yet.…”
Section: Scope Of Am For Fabricating Polymer Flow Field Platesmentioning
confidence: 99%
“…In terms of the reinforcement types, carbon fiber-reinforced polymer composites, carbon-carbon composites, hybrid composites, and structural composites have been created for the improvement of mechanical strength and electrical conductivity [ 23 , 24 ]. The structure composites can be divided into two categories which are sandwich panels and laminated composites [ 25 , 26 ]. In this work, the laminated composite was selected to produce an electrically conductive BP.…”
Section: Introductionmentioning
confidence: 99%